ISOLATION AND CHARACTERIZATION OF BACTERIA AND YEASTS FROM CONTAMINATED SOIL - Karlicic, Vera M; Radic, Danka S; Jovicic Petrovic, Jelena P.; Lalevic, Blazo T.; Jovanovic, Ljubinko M.; Kikovic, Dragan D.; Raicevic, Vera B. (Journal of Agricultural Sciences (Belgrade), 2016)
Plant growth promoting (PGP) bacteria and yeasts play an important role in bioremediation processes. Thirty bacterial and ten yeasts isolates were obtained from PAH and PCB contaminated soil with an aim of determining the presence of PGP mechanisms (production of ammonia, indole acetic acid, siderophores and solubilization of inorganic phosphate). As a result three bacterial (Serratia liquefaciens, Micrococcus sp. and Serratia sp.) and two yeasts isolates (Candida utilis and Candida tropicalis) stood up as PGP strains. Among them Serratia sp. showed the highest indole production (25.5 µg/ml). Analyses of metal tolerance (Cu+2, Cr+6 and Ni+2) revealed that Serratia liquefaciens, Micrococcus sp., Serratia sp. and Candida tropicalis were capable to tolerate significant concentration of metals. As a results of this study several bacterial and yeast strains were attributed as potential plant growth promoters which can be applied in future remediation activities and environmental quality improvements.